A Comparative Study of 50-Millesimal Potencies and Centesimal Potencies in the Treatment of Tinea Corporis: An Open, Randomised, Pilot Trial - Hazra, Pallavi; Mukherjee, Shyamal Kumar; Ganguly, Subhasish; Roy, Aniket Singha; Dutta, Souvik; Sadhukhan, Satarupa; Koley, Munmun; Saha, Subhranil (Homœopathic Links, 2021)
Introduction Standard management of dermatophytosis involves the use of topical antifungals in limited disease and oral therapy for more extensive cases. Despite the evidences favouring homeopathy in tinea corporis (TC) is inadequate, patients are increasingly opting for it. This trial attempts to assess the feasibility of a trial evaluating individualised homeopathic (IH) medicines in centesimal and 50-millesimal potencies in treating TC.Methods An open, randomised, pilot feasibility trial was conducted at the dermatology outpatient of D. N. De Homoeopathic Medical College and Hospital, West Bengal, India. Patients were randomised to receive IH medicines in either centesimal potencies (n = 30) or in 50-millesimal potencies (n = 30). Primary outcome measure was intensity of pruritus on a 0 to 10 numeric rating scale; secondary outcomes were Skindex-29 and dermatology life quality index questionnaires—all measured at baseline, and after 6 and 12 weeks of intervention. Group differences were calculated on intention-to-treat (ITT) sample as well as following per protocol (PP) analysis.Results Recruitment and attrition rates were 69 and 16.7% respectively. Both ITT and PP analysis revealed that intra-group changes in both the primary and secondary outcomes to be statistically significant in both the groups (all p < 0.05, one-way repeated measure analysis of variance). There were no significant group differences over 6 and 12 weeks (all p > 0.05, unpaired t-tests); thus, indicating similar pattern of improvement in both the groups. Most frequently used medicines were Natrum sulphuricum (28.3%), Natrum muriaticum (25%), Sulphur (8.3%) and Bacillinum (6.7%). No harms, unintended effects, homeopathic aggravations or any serious adverse events were reported from either group.Conclusion An adequately powered trial exploring effectiveness of both scales in TC appeared to be feasible in future. Though the sample size was too small to arrive at any definite conclusion, both centesimal and 50-millesimal potencies of IH medicines appeared to be equally useful in improving pruritus intensity and quality of life in patients suffering from TC.
Keywords: centesimal potency; 50-millesimal potency; homeopathy; pilot trial; randomised controlled trials; tinea corporis